Pengukuran Kesiapan Adopsi Teknologi Informasi (IT Adoption) Pada Gapoktan Hidup Baru Kec. Cempaka OKU Timur Dengan Metode Community Readiness Model - Akbaroka, Leo; Oktadini, Nabila Rizky; Marjusalinah, Anna Dwi; Sevtiyuni, Putri Eka; Az Zahra, Cindy Putri (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2024)
This research aims to measure the readiness to adopt information technology in the Gapoktan Life Baru community in East Cempaka OKU District using the Community Readiness Model (CRM) method. CRM measures several aspects, namely Community Effort, Knowledge Towards Issues, Leadership, Community Conditions, Community Knowledge, and Related Resources. This research involved 23 respondents who were members of the New Life Gapoktan. The research results show that the Community Effort (CE) aspect obtained a score of 3.86, Knowledge Towards Issue (KT) 3.32, Leadership (LS) 4.55, Community Conditions (KM) 3.89, Community Knowledge (PM) 3, 45, and Related Resources (ST) 4.06. Based on the overall score, the level of community readiness reached a final score of 3.86, which indicates that the community is at the initiation stage, which means efforts to adopt information technology have begun, but still require further strengthening. These results indicate that society has begun to realize the importance of implementing information technology, although more intensive efforts are still needed to achieve a higher level of readiness in adopting information technology optimally.